PENGGUNAAN SOFTWARE JURNAL.ID TERHADAP KINERJA KARYAWAN - Suci Astari Nurdzafira; Nuniek Dewi Pramanik (POLITEKNIK PIKSI GANESHA, 2022)
This study aims to determine the effect of the use of software Jurnal.id to employee performance at Micro, Small and Medium Enterprises in Bandung. With the Ease and the usefulness of the use of information technology as the perception researched in the Jurnal.id software. The research method used is quantitative associative. This research used a sample of 30 respondents with sampling using purposive sampling. The data collection technique is a questionnaire distributed to MSMEs in Bandung which uses Jurnal.id software. Based on the research results obtained using SPSS 25, test t, the results of the independent variables are obtained have t a count greater than t table, so that the independent variable has an influence on the dependent variable dependent. Then the results of the f test show that variable independent have a simultaneous effect on variable dependent with the result 151,254 > 3,354. Based on the results of the coefficient of determination obtained the value of R Square ( of 91.8%, which means that Employee Performance is influenced by the ease and the usefulness of the use of information technology Jurnal.id software.